PENGGUNAAN LIMBAH KULIT KACANG TANAH DALAM RANSUM TERHADAP PRODUKTIVITAS TERNAK SAPI JANTAN POTONG PERANAKAN FRIESIAN HOLSTEIN (PFH): THE USE OF PEANUT SHELL IN RATIONS ON THE PRODUCTIVITY OF FRIESIAN HOLSTEIN BEEF CATTLE - Nugroho, Agung; Purwadi, Purwadi; Suhardi, Suhardi (Universitas Boyolali, 2024)
This research aims to determine the effect of using peanut shell waste in rations on the productivity of Holstein Friesian crossbreed beef cattle (PFH). This research used 16 of Holstein Friesian crossbreed beef cattle average 1 years old and average body weight 415,28 + 8,98 kg (CV=2,1%). This research treatment was T0: peanut shell 0%, elephant grass 60%, rice brand 10%, tofu dregs 30%., T1: peanut shell 60%, elephant grass 0%, rice brand 10%, tofu dregs 30%. The parameter research are dry matter consumption, crude protein consumption, crude fat consumption, TDN consumption, daily weight gain, feed conversion and feed cost per gain. Based on the research results, it can be concluded that giving peanut shells can be used in fattening rations for PFH. The effect of giving peanut shells on Crude Protein (PK) consumption, TDN consumption, Feed Conversion was very significant (P<0.01). Dry matter consumption (BK) and daily body weight gain (PBBH) were not significantly (P> 0.05). Feed Cost Per Gain, is very significant (P<0.01), T1 is much cheaper than T0, so T1 is more profitable or more efficient.